PENGARUH LAMA CEDERA TENDINOPATI PATELLAR TERHADAP KEMAMPUAN VERTICAL JUMP PADA ATLET BASKET (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2019)
AbstractObjective: : This research aims to determine the effect of long-term injury of patellar tendinopathy on the ability of vertical jumps in basketball athletes. Method: this research is quantitative descriptive with the type of correlation study. Samples were selected using a purposive sampling technique. The sample consisted of 18 male and female basketball players from the Tunas Harapan club with the age category of 16 years to 23 years, with inculsion criteria. Still actively participating in training conducted by Tunas Harapan basketball club. Having a history of patellar tendinopathy or having a recurrent patellar tendinopathy injury, at least 1 month. where the duration of tendinopathy injury is measured using a questionnaire and the vertical jump ability test is measured using a sargent test. Results: The mean and standard deviation of the length of time for patellar tendinopathy injuries was 3.89 ± 2.74 calculated in months and the average vertical jump and standard deviation were 45.21 ± 8.46 calculated in centimeters. Normality test with Shapiro Wilk test obtained data with normal distribution. The results of hypothesis testing with Spearman rank correlation test showed p = 0.005 on injury time and vertical jump test and r = -0,718 with negative direction so the longer the injury the more it affects the ability of vertical jump in basketball athletes. Conclusion: There is a long-standing relationship of patellar tendinopathy injury to the ability of vertical jumps in basketball athletes. Keywords: Long-term of injury, vertical jump, sargent test Abstrak Tujuan: Penelitian ini untuk mengetahui pengaruh lama cedera tendinopati patellar terhadap kemampuan vertical jump pada atlet basket. Metode : penelitian ini bersifat deskriptif kuantitatif dengan tipe studi korelasi. Sampel dipilih menggunakan teknik purposive sampling . Sampel terdiri dari 18 orang pemain basket putra dan putri club tunas harapan dengan kategori umur 16 tahun sampai dengan 23 tahun ,dengan kriteria inkulsi Masih aktif mengikuti pelatihan yang dilakukan oleh Tunas Harapan basketball club. Memiliki riwayat tendinopati patellar atau memiliki cedera tendinopati patellar berulang, minimal sudah 1 bulan. dimana lama cedera tendinopati diukur menggunakan kuisoner dan tes kemampuan vertical jump diukur menggunakan sargent test. Hasil: Rata – rata dan standar deviasi waktu lama cedera tendinopati patellar bernilai 3,89±2,74 dihitung dalam bulan dan vertical jump rata – rata dan standar deviasi bernilai 45,21±8,46 dihitung dalam centimeter. Uji normalitas dengan Shapiro wilk test didapatkan data berdistribusi normal. Hasil uji hipotesis dengan uji korelasi Spearman rank correlation didapatkan p = 0,005 pada lama cedera dan tes vertical jump serta nilai r = -0,718 dengan arah negatif sehingga semakin lama cedera maka semakin mempengaruhi kemampuan vertical jump pada atlet basket.Kesimpulan : Ada hubungan lama cedera tendinopati patellar terhadap kemampuan vertical jump pada atlet basket. Kata kunci: Lama cedera, vertical jump, sargent test